Sebaceous Carcinoma: A Rare Extraocular Presentation of the Cheek - Ritu Swali; Crystal Nwannunu; Stephen Tyring (European Medical Journal, 2020)
Sebaceous carcinoma is a rare and aggressive malignant cutaneous cancer that arises from the sebaceous gland epithelium. This type of cancer typically presents in the periocular area and is rarely expressed in the extraocular space. The estimated overall incidence rate is one to two per million people per year. Sebaceous carcinoma tends to carry a delay in diagnosis as its variability in presentation of histologic growth patterns and diverse clinical presentation causes it to frequently be mistaken for common benign entities. Here, the authors report a case of a rare extraocular sebaceous carcinoma presenting on the cheek of a 78-year-old Caucasian male and discuss commonly mistaken differential diagnoses and the standard approach to properly diagnose and manage this rare tumour. Dermatologic literature has limited reference to sebaceous carcinoma, because this is rarely seen in an extraocular location, thus this case report provides a primary dermatologic perspective on this rare and aggressive skin cancer.